Interaction of the flow of flushing fluid with the drill pipes and the wall of the well - Kharchenko, Yevhen; Butrynskyi, Dmytro (Видавництво Львівської політехніки, 2024)
The steady-state flow of flushing fluid in the annular space of a drill pipe string in the case when the cross section of the channel is an eccentric ring is considered. The drilling mud is considered as a viscoplastic non-Newtonian fluid. The method for calculating the hydraulic parameters of the flushing fluid flow is based on the use of iterative methods of solving nonlinear equations and numerical analysis methods. The method can be used to calculate the hydraulic parameters of the flow in cases of laminar, structural and turbulent modes of fluid motion.
Keywords: drilling fluid flow; non-Newtonian fluid; eccentric annulus